Functional gradient silicon-based electrode and multi-layer composite coating method thereof
Through the multi-layer composite coating process, the functional gradient silicon-based electrode is designed, and the performance decay caused by the single-layer homogeneous electrode is solved, and a lithium-ion battery with high energy density and long life is realized.
Patent Information
- Application Number
- CN202411462100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The single-layer homogeneous silicon-based electrodes of existing lithium-ion batteries have severe performance decline due to volume effects, which cannot meet the needs of high energy density and long life.
The multi-layer composite coating process is used to design the functional gradient silicon-based electrode. By regulating the slurry characteristics and coating parameters, the coating of up to 6 layers can be achieved, avoid cracking problems, and optimize the internal structure of the active coating.
It significantly improves the cycling performance of silicon-based electrodes, alleviates stress mismatch, and improves the energy density and life of the battery.
Smart Images

Figure CN119480932A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a functional gradient silicon-based electrode and a multi-layer composite coating method thereof. Background Art
[0002] Lithium-ion batteries are a revolutionary innovation in the energy field. They have the advantages of light weight, small size, high capacity, long life and low environmental pollution. They have promoted the leapfrog development of emerging industries such as new energy vehicles, and have been applied to strategic fields such as satellites and drones, becoming the focus of scientific and technological development. At present, with the gradual development of pure electric aircraft, the construction of the low-altitude economic industrial system and the rapid development of pure electric vehicles, the requirements for the energy density of single power batteries are getting higher and higher. Existing lithium-ion batteries can no longer meet people's technical needs for high energy density and new high-performance batteries.
[0003] Among the components that make up lithium-ion batteries, negative electrode materials are an important factor affecting battery capacity and battery life. At present, commercial lithium-ion battery negative electrode materials (mainly carbon materials such as graphite) are close to the theoretical capacity limit and cannot meet the needs of the development of high-energy density batteries. Therefore, the use of new materials is the key to improving battery energy density. Compared with graphite negative electrodes, silicon-based negative electrodes can increase battery energy density by 4 to 10 times and improve battery charging performance. According to the forecast of battery energy research company SNE Research, the global penetration rate of silicon negative electrodes will increase from 1% in 2023 to 5% in 2025. By 2030 and 2035, the market share of silicon-based negative electrodes is expected to reach 7% and 10% respectively. As electric vehicle manufacturers and battery manufacturers increase their requirements for the range and fast charging performance of electric vehicles, it is expected that the competition for silicon-based negative electrodes will gradually unfold starting from 2024.
[0004] The reaction mechanism of silicon and lithium is through intermetallic alloying. This reaction can provide almost ten times the capacity of graphite, thereby increasing the energy density of the battery. However, silicon will expand in volume (>300%) when alloying with lithium, causing silicon particles to be subjected to large hoop tensile stress, making them easy to pulverize and free. At the same time, the volume effect of silicon also damages the entire conductive network, and the shear stress caused by uneven deformation causes the active layer of the current collector interface to peel off. In addition, the volume change will also lead to dynamic changes in the electrode-electrolyte interface, further deteriorating and thickening the solid electrolyte interface. The performance degradation of silicon-based electrode lithium-ion batteries is mainly caused by the loss of active substances, active lithium loss and polarization loss caused by the above-mentioned mechanical degradation, chemical degradation and the mutual coupling between the two.
[0005] In order to solve these problems, people have proposed technologies such as coating structure, hollow structure and changing the surface morphology of current collector. However, these methods have some limitations and defects, such as carbon coating cannot inhibit the fracture of silicon particles, the manufacturing process of porous silicon or core-shell structure is complicated and not suitable for industrial production, and the manufacturing process of changing the surface morphology of current collector is complicated and costly. The use of nano silicon particles can effectively alleviate the volume effect. For example, for silicon particles with a particle size of less than 150nm, the stored strain energy of the electrochemical reaction is not enough to drive crack propagation, avoiding the silicon expansion and fracture caused by lithiation, but the continuous reduction of particle size means higher production costs, and it will also have a negative impact on battery performance. For example, the high specific surface area brings about a lower first-cycle Coulomb efficiency (50% to 85%), which restricts its commercial application process. In addition, the current lithium-ion battery basically uses a single-layer homogeneous electrode dried and formed by a one-time coating process. Due to the change in porosity / tortuosity caused by the expansion of silicon lithiation, the ionic conductivity / diffusion performance changes, resulting in low utilization of active materials on the current collector side, and the excessive shear stress caused by the expansion of silicon lithiation is easy to cause stress mismatch at the coating / current collector interface. Therefore, there is currently a lack of an economical and effective method to improve the performance of single-layer homogeneous silicon-based electrode lithium-ion batteries.
[0006] Traditional electrodes have unstable electrode surfaces and internal structures and severe electrode polarization due to their single-layer structures, which to some extent limit the performance of high-load and high-capacity electrodes. How to improve battery performance while maintaining the overall component content is a common problem faced by academia and industry. Inspired by the fact that the reinforcing phase in many natural biocomposites is distributed in a gradient in the matrix structure, which conforms to the principle of using the least material and the simplest structure to achieve the maximum efficiency, the design concept of functional gradient was proposed. At present, academia and industry have designed and manufactured double-layer gradient or even triple-layer gradient electrodes. Functional gradient electrodes combine the design concept of functional gradient materials into electrodes. It is a new solution to electrode performance degradation. It can improve the cycle performance of silicon-based electrodes without complex material modification. At the same time, through the multi-layer gradient optimized electrode structure, it can alleviate the stress mismatch phenomenon of silicon-based electrodes during the charging and discharging process, thereby promoting the application of high-energy-density silicon-based electrode lithium-ion batteries.
[0007] Therefore, in view of the problems existing in the current single-layer homogeneous electrode, it is particularly important to develop a multi-layer composite coating process and design a functional gradient silicon-based electrode with excellent performance to promote the healthy development of high energy density batteries. The present invention proposes a multi-layer composite coating process, especially a five-layer coating process, and designs several functional gradient silicon-based electrodes. Through implementation and testing, it is found that under the same active material mass ratio (wt%), the functional gradient design significantly improves the problem of silicon-based electrode capacity decay, proving the feasibility of the multi-layer composite coating process and the superiority of the designed functional gradient silicon-based electrode.
[0008] The battery pole piece is composed of a metal current collector and an active coating. The active coating is a porous composite material. Its microstructure includes active material particles, areas where the conductive agent and the binder are mixed (carbon gel phase), and microscopic pore spaces between the solid phases. These pores need to be filled with electrolyte. During the charge and discharge process of lithium-ion batteries, the concentration gradient generated by the lithium ion diffusion process and the deformation caused by the lithium expansion of the active material will cause diffusion stress. Excessive diffusion stress will cause multiple mechanical failure forms such as the rupture of the active material, the separation between the active materials, the fracture of the active layer, and the stratification of the active layer and the current collector, and ultimately lead to a series of failure phenomena such as capacity decay, impedance increase, and shortened life of the battery. This phenomenon is particularly serious in silicon-based electrodes. However, the volume deformation of silicon materials and their unstable SEI film are their intrinsic problems; at the same time, the instability of the upper and lower surfaces of the electrode active coating and the overall instability of the electrode structure caused by internal polarization are intrinsic problems of traditional single-layer electrode structures. Therefore, for single-layer silicon electrodes, as the charge and discharge cycles proceed, the result is a significant deterioration of the electrode structure and a significant decay of the capacity, thereby shortening the battery life.
[0009] However, graphite negative electrode lithium-ion batteries cannot meet the requirements of high energy density. The performance of single-layer homogeneous silicon-based electrodes is seriously degraded due to their volume effect, mainly including the following three technical problems:
[0010] 1. Inherent problems of homogeneous silicon-based electrodes: insufficient utilization of active materials, poor structural stability, rapid mechanical and chemical degradation, and rapid capacity decay.
[0011] 2. Functional gradient electrode design issues: In view of the impact of each component on electrode performance and the competition between multiple components, how to regulate the components and use the functional gradient design concept to design silicon-based electrodes that can improve mechanical and electrochemical properties are key technical issues.
[0012] 3. The problem of cracking in multi-layer electrode coating: In order to achieve a better and more continuous gradient design, the current 2-3 layer coating is no longer sufficient. However, when more layers of coating are applied, especially five layers or more, cracking and peeling of the coating is difficult to avoid due to the accumulation of stress and strain during drying. Considering the feasibility and economy, how to prepare a composite electrode containing multiple layers of electrode active layers and implement high-quality 4-5 layers of composite coating is a key technical issue. Summary of the invention
[0013] The present invention is made to solve the above problems, and its purpose is to provide a functional gradient silicon-based electrode and a multi-layer composite coating method thereof.
[0014] The present invention provides a multilayer composite coating method for a functional gradient silicon-based electrode, which has the following characteristics:
[0015] S1. Weigh the binder, the conductive agent and the active material, mix the weighed binder and the solvent to form a glue solution, then dry-mix the active material and the conductive agent and mix them with the glue solution for 2 to 4 hours to obtain a slurry. The slurry is divided into five slurries according to the proportion of the active material, which are respectively recorded as slurry layer 1, slurry layer 2, slurry layer 3, slurry layer 4 and slurry layer 5;
[0016] S2. The slurry layer is coated on a copper foil of 9 to 15 μm, the single layer coating thickness is 40 to 100 μm, the coating speed is 2 to 6 mm / s, and the coating is dried after completion, the drying temperature is 70 to 100 ° C, and the drying time is 10 to 30 minutes;
[0017] S3. Coating a slurry layer 2 on the basis of a slurry layer, a single layer coating thickness of 40 to 100 μm, a coating speed of 2 to 6 mm / s, a coating width should be greater than the width of the slurry layer of at least 2 mm, after the coating is completed, drying, the drying temperature is 70 to 100 ° C, the drying time is 10 to 30 minutes;
[0018] S4. Coating a slurry layer three on the basis of the slurry layer two, the single layer coating thickness is 40 to 100 μm, the coating speed is 2 to 6 mm / s, the coating width should be greater than the width of the slurry layer two by at least 2 mm, and the coating is dried after completion, the drying temperature is 70 to 100 ° C, and the drying time is 10 to 30 minutes;
[0019] S5. Coating a slurry layer four on the basis of the slurry layer three, the single-layer coating thickness is 40 to 100 μm, the coating speed is 2 to 6 mm / s, the coating width should be at least 2 mm greater than the width of the slurry layer three, and the coating is dried after the coating is completed, the drying temperature is 70 to 100 ° C, and the drying time is 10 to 30 minutes;
[0020] S6. Coating a slurry layer V on the basis of the slurry layer IV, the single-layer coating thickness is 40 to 100 μm, the coating speed is 2 to 6 mm / s, the coating width should be greater than the width of the slurry layer IV by at least 2 mm, and the coating is dried after completion, the drying temperature is 70 to 100 ° C, and the drying time is 10 to 30 minutes;
[0021] S7. The copper foil finally coated with five layers of slurry is dried in a vacuum oven at 70-90° C. for 6-8 hours, and then placed in a room for 46-50 hours for aging before use.
[0022] In the multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein the slurry viscosity is 1200-2400 mPa·s, the viscosity of slurry layer one is 2000-2400 mPa·s, and the viscosity of slurry layer five is 1200-1500 mPa·s.
[0023] The multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention may also have the following characteristics: wherein the viscosity of the slurry layer 2, the slurry layer 3 and the slurry layer 4 is 1500-2000 mPa·s.
[0024] In the multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein the binder is a polyacrylic acid binder or a sodium alginate binder, the solvent is deionized water, the active substance is nano-silicon particles, and the conductive agent is conductive carbon black, single-arm carbon nanotubes, or a mixture of conductive carbon black and single-arm carbon nanotubes.
[0025] In the multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein, the nano-silicon particles in the slurry layer one account for 10wt%, the nano-silicon particles in the slurry layer two account for 20wt%, the nano-silicon particles in the slurry layer three account for 30wt%, the nano-silicon particles in the slurry layer four account for 40wt%, and the nano-silicon particles in the slurry layer five account for 50wt%.
[0026] In the multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein, the average particle size of the nano-silicon particles in the slurry layer one is 50nm, the average particle size of the nano-silicon particles in the slurry layer two is 100nm, the average particle size of the nano-silicon particles in the slurry layer three is 100nm, the average particle size of the nano-silicon particles in the slurry layer four is 150nm, and the average particle size of the nano-silicon particles in the slurry layer five is 150nm.
[0027] In the multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein, the nano-silicon particles in the slurry layer one account for 10wt%, the nano-silicon particles in the slurry layer two account for 40wt%, the nano-silicon particles in the slurry layer three account for 50wt%, the nano-silicon particles in the slurry layer four account for 40wt%, and the nano-silicon particles in the slurry layer five account for 10wt%.
[0028] In the multilayer composite coating method of the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein, the average particle size of the nano-silicon particles in the slurry layer one is 50nm, the average particle size of the nano-silicon particles in the slurry layer two is 100nm, the average particle size of the nano-silicon particles in the slurry layer three is 150nm, the average particle size of the nano-silicon particles in the slurry layer four is 100nm, and the average particle size of the nano-silicon particles in the slurry layer five is 50nm.
[0029] The present invention also provides a functional gradient silicon-based electrode, which is obtained by the multi-layer composite coating method of the functional gradient silicon-based electrode.
[0030] In the functional gradient silicon-based electrode provided by the present invention, it can also have the following characteristics: wherein, the functional gradient silicon-based electrode includes: a metal current collector and an active coating, the metal current collector is copper foil, and the active coating is slurry layer one, slurry layer two, slurry layer three, slurry layer four and slurry layer five.
[0031] Functions and Effects of the Invention
[0032] The functional gradient silicon-based electrode and the multilayer composite coating method thereof according to the present invention can achieve:
[0033] 1. Avoid cracking problems in multi-layer coating: The traditional multi-layer coating process has a small number of coating layers (2 to 3 layers), and may cause cracking due to problems with slurry properties and coating parameters. At the same time, new coating equipment needs to be developed. The multi-layer composite coating process proposed in the present invention provides a multi-layer composite coating process that can avoid cracking by regulating slurry properties and coating parameters, and can perform up to 6 layers of coating, thereby improving the possibility of optimizing the hierarchical design of functional gradient electrodes.
[0034] 2. Optimizing the performance of single-layer homogeneous silicon-based electrodes: Traditional single-layer homogeneous silicon-based electrodes have instability in the electrode surface and internal structure, which leads to rapid degradation of mechanical coupling and limits their high load and high capacity performance. Uneven utilization of active coating components and electrode polarization are inevitable problems of traditional electrodes in operation. The above problems can be alleviated by reasonable design of the internal structure of the active coating. The two types of functionally gradient silicon-based electrodes involved in the present invention have excellent cycle performance after experimental verification, indicating that functionally gradient electrodes are an effective and cost-effective solution to improve homogeneous electrodes.
[0035] 3. Improve the energy density of lithium-ion batteries: Due to material limitations and structural design challenges, existing lithium-ion batteries are difficult to achieve higher energy density. The functionally gradient silicon-based electrode implemented by the multi-layer composite coating process proposed by the present invention can improve the utilization rate of electrode active materials and more effectively utilize the high capacity characteristics of silicon. At the same time, it improves the inherent problems of homogeneous silicon-based electrodes and improves the performance of high energy density silicon-based electrode lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the structure of a functionally gradient silicon-based electrode in Example 1 of the present invention;
[0037] Figure 2 This is a schematic diagram of the structure of a functionally gradient silicon-based electrode in Example 2 of the present invention;
[0038] Figure 3 This is a schematic structural diagram of a functionally gradient silicon-based electrode in Example 3 of the present invention;
[0039] Figure 4 This is a conceptual diagram of the gradient components of a functionally gradient silicon-based electrode in Example 1 of the present invention;
[0040] Figure 5 This is a conceptual diagram of the gradient components of a functionally gradient silicon-based electrode in Example 2 of the present invention;
[0041] Figure 6 This is a conceptual diagram of the gradient components of a functionally gradient silicon-based electrode in Example 3 of the present invention;
[0042] Figure 7 This is a comparison chart of the cycle capacity of three embodiments of the present invention at a rate of 0.2C;
[0043] Figure 8 A capacity-voltage comparison diagram of an embodiment of the fifth cycle stage of the present invention; and
[0044] Fig. 9 This is the actual coating effect of the multi-layer composite coating process of the present invention. DETAILED DESCRIPTION
[0045] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments and the accompanying drawings specifically illustrate the functional gradient silicon-based electrode and the multi-layer composite coating method thereof of the present invention.
[0046] Example 1
[0047] The functionally gradient silicon-based electrode 100 of Example 1 is realized by the following multi-layer composite coating method:
[0048] S1. Weigh 10wt% of nano silicon particles 11 (average particle size 50nm), 68wt% of conductive carbon black and 22wt% of sodium alginate, mix the weighed sodium alginate with a certain proportion of deionized water to form a glue, then dry-mix the nano silicon particles and the conductive carbon black and mix them with the glue to form a slurry. The slurry is stirred for 3 hours. The slurry viscosity is adjusted by adding deionized water so that the adjusted slurry viscosity is between 2200mPa·s to form a slurry layer 10.
[0049] 20wt% of nano silicon particles 21 (average particle size 100nm), 60wt% of conductive carbon black and 20wt% of sodium alginate are weighed, and the weighed sodium alginate is mixed with a certain proportion of deionized water to form a glue solution, and then the nano silicon particles and the conductive carbon black are dry-mixed and mixed with the glue solution to form a slurry, and the slurry is stirred for 3 hours. The slurry viscosity is adjusted by adding deionized water to make the adjusted slurry viscosity 1500mPa·s to prepare the slurry of the slurry layer 20.
[0050] 30wt% of nano silicon particles 31 (average particle size 100nm), 50wt% of conductive carbon black and 20wt% of sodium alginate were weighed, and the weighed sodium alginate was mixed with a certain proportion of deionized water to form a glue solution, and then the nano silicon particles and the conductive carbon black were dry-mixed and mixed with the glue solution to form a slurry, and the slurry was stirred for 3 hours. The slurry viscosity was adjusted by adding deionized water to make the adjusted slurry viscosity 1700mPa·s to prepare the slurry of the slurry layer 30.
[0051] 40wt% of nano silicon particles 41 (average particle size 150nm), 40wt% of conductive carbon black and 20wt% of sodium alginate were weighed, and the weighed sodium alginate was mixed with a certain proportion of deionized water to form a glue solution, and then the nano silicon particles and the conductive carbon black were dry-mixed and mixed with the glue solution to form a slurry, and the slurry was stirred for 3 hours. The slurry viscosity was adjusted by adding deionized water to make the adjusted slurry viscosity 2000mPa·s to prepare a slurry layer 40.
[0052] 50wt% of nano silicon particles 51 (average particle size 150nm), 30wt% of conductive carbon black and 20wt% of sodium alginate were weighed, and the weighed sodium alginate was mixed with a certain proportion of deionized water to make a glue solution, and then the nano silicon particles and the conductive carbon black were dry-mixed and mixed with the glue solution to make a slurry, and 0.05%wt of single-arm carbon nanotubes were added at the same time. The slurry was stirred for 3 hours. The slurry viscosity was adjusted by adding deionized water, and the adjusted slurry viscosity was between 1300mPa·s to make a slurry with a slurry layer of 50.
[0053] S2. The slurry layer 10 is coated on a 9μm copper foil 60, a single layer coating thickness of 65μm, a coating speed of 2mm / s, and the coating is dried immediately after completion, the drying temperature is 80 ℃, and the drying time is 15 minutes;
[0054] S3. A slurry layer 10 is coated on the basis of a slurry layer 20, a single-layer coating thickness of 70μm, a coating speed of 3mm / s, a coating width greater than the previous coating width of 2mm, and the coating is dried immediately after completion, the drying temperature is 80 ℃, and the drying time is 15 minutes;
[0055] S4. On the basis of the slurry layer 20, a slurry layer 30 is coated on the second layer, the single layer coating thickness is 70μm, the coating speed is 3mm / s, the coating width is greater than the previous coating width 2mm, and the coating is dried immediately after completion, the drying temperature is 80 ℃, and the drying time is 15 minutes;
[0056] S5. On the basis of the slurry layer three 30, a slurry layer four 40 is coated, the single layer coating thickness is 70μm, the coating speed is 3mm / s, the coating width is greater than the previous coating width 2mm, and the coating is dried immediately after completion, the drying temperature is 80 ℃, and the drying time is 15 minutes;
[0057] S6. A slurry layer 50 is coated on the basis of four slurry layers 40, a single-layer coating thickness of 75μm, a coating speed of 3mm / s, a coating width greater than the previous coating width of 2mm, and drying is performed immediately after coating is completed, the drying temperature is 80 ℃, and the drying time is 15 minutes;
[0058] S7. The electrode finally coated with five layers of slurry is dried at 80°C in vacuum for 6 hours, and then placed in a room environment for 48 hours for aging.
[0059] Figure 1 This is a schematic diagram of the structure of a functionally gradient silicon-based electrode in Example 1 of the present invention. Figure 4 This is a conceptual diagram of the gradient components of a functionally gradient silicon-based electrode in Example 1 of the present invention.
[0060] like Figure 1-2 As shown, this is the slurry layer obtained after coating in Example 1. In Example 1, the high silicon content layer is positioned close to the diaphragm to achieve the shortest path for ions to travel back and forth between the high silicon content layer, thereby improving the utilization rate of active materials compared to homogeneous electrodes with the same silicon content. In Example 1, large-size silicon nanoparticles are positioned close to the diaphragm. Under the same content of active materials, the larger the particles, the larger the pore size, and the smaller the tortuosity. The large-particle silicon close to the diaphragm enhances the liquid phase diffusion capacity from the diaphragm / electrode interface to the inside.
[0061] The prepared and aged electrode was vacuum dried at 90°C for 12 hours, the water content of the electrode was controlled to be below 200 ppm, and the processed electrode was punched into a disc with a diameter of 12 mm.
[0062] The obtained circular electrode was weighed and the average load of the active coating was measured to be: 2.4 mg / cm 2 Since the total mass of nano-silicon particles accounts for 30wt%, the silicon loading is 0.72mg / cm 2 Arrange the components of CR2032 battery (including positive electrode shell, negative electrode shell, circular gasket, spring, diaphragm, silicon-based electrode disc, lithium disc, electrolyte), adjust the gas and air pressure in the glove box (water vapor and oxygen content in the glove box ≤ 0.1ppm), and assemble the button battery in sequence. The electrolyte is 1M LiPF6 (EC:DEC=3:7, 10% FEC), and the diaphragm is Celgard2320. Set aside the assembled battery for 12 hours to allow the electrolyte to fully infiltrate.
[0063] The set-aside batteries were subjected to cyclic voltammetry tests. Before the test, they were first formed with a formation current of 0.1C and cycled 5 times. After the formation, a cycle test was performed with a test voltage range of 0.01V to 1V and a test current of 0.2C constant current charge and discharge.
[0064] Example 2
[0065] Based on the multilayer composite coating method of the functional gradient silicon-based electrode 100 of Example 1, the slurry of the second slurry layer 20' of the functional gradient silicon-based electrode 100' in Example 2 weighs 40wt% of silicon nanoparticles 21' (average particle size 100nm), 40wt% of conductive carbon black and 20wt% of sodium alginate; the slurry of the third slurry layer 30' weighs 50wt% of silicon nanoparticles 31' (average particle size 150nm), 30wt% of conductive carbon black and 20wt% of sodium alginate; the slurry of the fourth slurry layer 40' weighs 40wt% of silicon nanoparticles 41' (average particle size 100nm), 40wt% of conductive carbon black and 20wt% of sodium alginate; the slurry of the fifth slurry layer 50' weighs 10wt% of silicon nanoparticles 51' (average particle size 50nm), 70wt% of conductive carbon black and 20wt% of sodium alginate.
[0066] Figure 2 This is a schematic diagram of the structure of a functionally gradient silicon-based electrode in Example 2 of the present invention. Figure 5 This is a conceptual diagram of the gradient components of a functionally gradient silicon-based electrode in Example 2 of the present invention.
[0067] like Figure 2 , 5 As shown, it is the slurry layer obtained after coating of Example 2. In Example 2, the high silicon content layer and large-size silicon nanoparticles are positioned in the middle layer of the electrode, and the low silicon content layer and small-size nano-silicon are positioned on the side of the electrode close to the metal current collector and the side close to the diaphragm, forming a "sandwich" structure with high silicon content in the middle and low silicon content on both sides. Due to the volume effect of the silicon electrode, cracks will appear on the surface of the electrode after multiple cycles, and the cracks will gradually expand as the number of cycles increases, and finally cause the battery capacity to decline rapidly. In Example 2, by coating the low silicon content layer (slurry layer five) on the middle high silicon content layer (slurry layer two, slurry layer three, slurry layer four), the cracking of the electrode surface caused by the expansion of silicon particles is alleviated. At the same time, the low silicon content layer means a high conductive agent layer. With the help of the agglomeration of the conductive carbon black itself, a higher porosity will be formed, which is also conducive to the diffusion of the electrolyte to the middle high silicon content layer.
[0068] Comparative Example 1
[0069] Based on the multi-layer composite coating method of the functional gradient silicon-based electrode 100 of Example 1, the slurry of each slurry layer (10", 20", 30", 40", 50") in the functional gradient silicon-based electrode 100" of Comparative Example 1 is weighed with 30wt% of silicon nanoparticles (11", 21", 31", 41", 51") (average particle size 100nm).
[0070] Figure 3 This is a schematic diagram of the structure of a functionally gradient silicon-based electrode in Comparative Example 1 of the present invention. Figure 6 This is a conceptual diagram of the gradient components of a functionally gradient silicon-based electrode in Comparative Example 1 of the present invention.
[0071] like Figure 3 , 6 Shown is the slurry layer obtained after coating of Comparative Example 1.
[0072] Figure 7 The figure is a comparison chart of the cycle capacity of three embodiments of the present invention at a rate of 0.2C. Figure 8 This is a capacity-voltage comparison diagram of an embodiment of the fifth cycle stage of the present invention. Fig. 9 This is the actual coating effect of the multi-layer composite coating process of the present invention.
[0073] like Figure 1-9 As shown, both Example 1 and Example 2 of the present invention are designed with a bonding buffer layer near the metal current collector side, while Comparative Example 1 is not designed with a bonding buffer layer.
[0074] The bonding buffer layer, i.e. the low silicon content layer on the metal current collector side, improves the problem that the active material far away from the diaphragm cannot fully utilize its capacity. At the same time, the low silicon content makes the volume expansion very small, which can effectively avoid the direct influence of the volume effect of silicon particles on the coating / metal current collector interface. By appropriately increasing the binder content in this layer, it plays an overall bonding buffer role, reduces stress concentration, and reduces the possibility of coating peeling. The low silicon content layer has a high content of conductive agent, which can form more conductive paths, which is conducive to the formation of a high-speed conductive network.
[0075] In addition, both Example 1 and Example 2 of the present invention add single-arm carbon nanotubes to the coating near the diaphragm side, and adding ≤0.1%wt single-walled carbon nanotubes to the slurry can improve the conductivity and mechanical stability of the electrode active layer. In particular, adding single-armed carbon nanotubes to the active layer on the electrode surface near the diaphragm can greatly improve the stability of the coating and form a protective layer. Nanosilicon is dispersed in an amorphous porous carbon skeleton composed of single-walled carbon nanotubes and conductive carbon black, avoiding agglomeration between silicon nanoparticles. The 3D conductive network formed by the porous carbon skeleton can also accommodate the volume expansion of nanosilicon particles and promote electron migration.
[0076] Functions and Effects of the Embodiments
[0077] The functional gradient silicon-based electrode and the multilayer composite coating method thereof according to the present invention can achieve:
[0078] 1. Avoid cracking problems in multi-layer coating: The traditional multi-layer coating process has a small number of coating layers (2 to 3 layers), and may cause cracking due to problems with slurry properties and coating parameters. At the same time, new coating equipment needs to be developed. The multi-layer composite coating process proposed in the present invention provides a multi-layer composite coating process that can avoid cracking by regulating slurry properties and coating parameters, and can perform up to 6 layers of coating, thereby improving the possibility of optimizing the hierarchical design of functional gradient electrodes.
[0079] 2. Optimizing the performance of single-layer homogeneous silicon-based electrodes: Traditional single-layer homogeneous silicon-based electrodes have instability in the electrode surface and internal structure, which leads to rapid degradation of mechanical coupling and limits their high load and high capacity performance. Uneven utilization of active coating components and electrode polarization are inevitable problems of traditional electrodes in operation. The above problems can be alleviated by reasonable design of the internal structure of the active coating. The two types of functionally gradient silicon-based electrodes involved in the present invention have excellent cycle performance after experimental verification, indicating that functionally gradient electrodes are an effective and cost-effective solution to improve homogeneous electrodes.
[0080] 3. Improve the energy density of lithium-ion batteries: Due to material limitations and structural design challenges, existing lithium-ion batteries are difficult to achieve higher energy density. The functional gradient silicon-based electrode implemented by the multi-layer composite coating process proposed in the present invention can improve the utilization rate of electrode active materials and more effectively utilize the high capacity characteristics of silicon. At the same time, it improves the inherent problems of homogeneous silicon-based electrodes and improves the performance of high energy density silicon-based electrode lithium-ion batteries.
[0081] The functional gradient electrode implemented by the present invention does not need to be rolled. A higher initial porosity can be formed through the multi-layer composite coating process proposed by the present invention. Due to the high theoretical specific capacity of silicon itself, the volume expansion after lithiation can reach 300%. The lower initial porosity may be filled after the silicon is expanded after lithiation. The closure of the pores will prevent lithium ions from diffusing, and the contact and extrusion between particles will cause a large stress concentration, which can easily cause the battery capacity to "dive". Therefore, a higher initial porosity is required to reserve expansion space, so there is no need for rolling.
[0082] The multi-layer composite coating process proposed in the present invention controls the mixing order, time, and solid content of the slurry, adjusts the viscosity of the slurry close to the current collector side to form a denser base coating with good surface quality at the bottom, and adjusts the viscosity of the slurry close to the diaphragm side to have good fluidity and leveling during the top coating process without damaging the existing coating due to the slurry being too viscous to be coated or being too diluted, and increases the coating width of each layer to avoid the thick edge problem caused by coating with the same width. There is no need to design additional coating equipment, and multi-layer coating can be achieved under the existing production system by only adjusting process parameters such as slurry viscosity and coating width.
[0083] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A multilayer composite coating method for a functionally gradient silicon-based electrode, characterized in that: The specific method is as follows: S1. Weigh the binder, the conductive agent and the active material, mix the weighed binder and the solvent to form a glue solution, then dry-mix the active material and the conductive agent and mix them with the glue solution for 2 to 4 hours to obtain a slurry. The slurry is divided into five slurries according to the proportion of the active material, which are respectively recorded as slurry layer 1, slurry layer 2, slurry layer 3, slurry layer 4 and slurry layer 5; S2. The slurry layer is coated on a copper foil of 9 to 15 μm, with a single layer coating thickness of 40 to 100 μm, a coating speed of 2 to 6 mm / s, and after coating, the coating is dried at a temperature of 70 to 100 ° C and a drying time of 10 to 30 minutes; S3. Coating a slurry layer 2 on the basis of the slurry layer 1, the single layer coating thickness is 40 to 100 μm, the coating speed is 2 to 6 mm / s, the coating width should be greater than the width of the slurry layer 1 by at least 2 mm, and the coating is dried after completion, the drying temperature is 70 to 100 ° C, and the drying time is 10 to 30 minutes; S4. Coating a slurry layer three on the basis of the slurry layer two, the single layer coating thickness is 40 to 100 μm, the coating speed is 2 to 6 mm / s, the coating width should be greater than the width of the slurry layer two at least 2 mm, after the coating is completed, the drying temperature is 70 to 100 ° C, the drying time is 10 to 30 minutes; S5. Coating a slurry layer four on the basis of the slurry layer three, the single layer coating thickness 40 ~ 100μm, the coating speed is 2 ~ 6mm / s, the coating width should be greater than the width of the slurry layer three at least 2mm, after the coating is completed, drying, the drying temperature is 70 ~ 100 ℃, the drying time 10 to 30 minutes; S6. Coating a slurry layer five on the basis of the slurry layer four, a single-layer coating thickness of 40 to 100 μm, a coating speed of 2 to 6 mm / s, a coating width should be greater than the width of the slurry layer four at least 2 mm, after the coating is completed, drying, the drying temperature is 70 to 100 ° C, the drying time is 10 to 30 minutes; S7. The copper foil finally coated with five layers of slurry is dried in a vacuum oven at 70-90° C. for 6-8 hours, and then placed in a room for 46-50 hours for aging before use.
2. The multilayer composite coating method of functionally gradient silicon-based electrodes according to claim 1, characterized in that: in, The viscosity of the slurry is 1200-2400 mPa·s, the viscosity of the slurry layer 1 is 2000-2400 mPa·s, and the viscosity of the slurry layer 5 is 1200-1500 mPa·s.
3. The multilayer composite coating method of functionally gradient silicon-based electrodes according to claim 2, characterized in that: in, The viscosity of the second slurry layer, the third slurry layer and the fourth slurry layer is 1500-2000 mPa·s.
4. The multilayer composite coating method of functionally gradient silicon-based electrodes according to claim 1, characterized in that: in, The binder is a polyacrylic acid binder or a sodium alginate binder, the solvent is deionized water, the active substance is nano silicon particles, and the conductive agent is conductive carbon black, single-arm carbon nanotubes, or a mixture of conductive carbon black and single-arm carbon nanotubes.
5. The multilayer composite coating method of functionally gradient silicon-based electrodes according to claim 1, characterized in that: in, The silicon nanoparticles in the first slurry layer account for 10 wt %, the silicon nanoparticles in the second slurry layer account for 20 wt %, the silicon nanoparticles in the third slurry layer account for 30 wt %, the silicon nanoparticles in the fourth slurry layer account for 40 wt %, and the silicon nanoparticles in the fifth slurry layer account for 50 wt %.
6. The multilayer composite coating method of functionally gradient silicon-based electrodes according to claim 5, characterized in that: in, The average particle size of the silicon nanoparticles in the slurry layer one is 50 nm, the average particle size of the silicon nanoparticles in the slurry layer two is 100 nm, the average particle size of the silicon nanoparticles in the slurry layer three is 100 nm, the average particle size of the silicon nanoparticles in the slurry layer four is 150 nm, and the average particle size of the silicon nanoparticles in the slurry layer five is 150 nm.
7. The multilayer composite coating method of functionally gradient silicon-based electrodes according to claim 1, characterized in that: in, The silicon nanoparticles in the first slurry layer account for 10 wt %, the silicon nanoparticles in the second slurry layer account for 40 wt %, the silicon nanoparticles in the third slurry layer account for 50 wt %, the silicon nanoparticles in the fourth slurry layer account for 40 wt %, and the silicon nanoparticles in the fifth slurry layer account for 10 wt %.
8. The multi-layer composite coating method of functionally gradient silicon-based electrodes according to claim 7, characterized in that: in, The average particle size of the silicon nanoparticles in the slurry layer one is 50 nm, the average particle size of the silicon nanoparticles in the slurry layer two is 100 nm, the average particle size of the silicon nanoparticles in the slurry layer three is 150 nm, the average particle size of the silicon nanoparticles in the slurry layer four is 100 nm, and the average particle size of the silicon nanoparticles in the slurry layer five is 50 nm.
9. The functionally gradient silicon-based electrode according to claim 1, characterized in that: The method is obtained by the multilayer composite coating method of the functional gradient silicon-based electrode according to any one of claims 1 to 9.
10. The functionally gradient silicon-based electrode according to claim 1, characterized in that: in, The functional gradient silicon-based electrode comprises: a metal current collector and an active coating, wherein the metal current collector is a copper foil, and the active coating comprises a slurry layer one, a slurry layer two, a slurry layer three, a slurry layer four and a slurry layer five.
Citation Information
Patent Citations
All-solid-state lithium battery with gradient structure and preparation method thereof
CN103746089A
Multilayer cathode sheet, method for producing cathode sheet and lithium ion battery
CN104538584A
Composite positive pole piece and lithium secondary battery
CN112825349A
Multi-layer coated battery pole piece and preparation method thereof
CN115832203A
Layered composite pole piece and preparation method thereof, lithium ion capacitor and lithium ion battery
CN118486782A